THE GREEN WORLD IN A GLASS VESSEL (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Florarium is an amazing combination of plants and glass, creating miniature ecosystems in an enclosed space. This trendy decorative element not only brings beauty to the interior, but also allows you to enjoy wildlife in any space. The article discusses the creation of florariums, which types of plants are suitable for growing in them, as well as their advantages. However, there are some problems that need to be taken into account so that the florarium does not lose its beauty.